Call for action to eradicate peste des petits ruminants: Evidence from Senegal - Kotchofa, Pacem (International Livestock Research Institute, 2021)
Pacem Kotchofa, agricultural economist at ILRI Senegal, presented this call for action to eradicate Peste des petits ruminants and improve the livelihoods of smallholder farmers in developing countries on 2 October 2021 for the World Food Forum, Transformative Research Challenge Final.